Managerial accounting for managers - Noreen, Eric W.; Brewer, Peter C.; Garrison, Ray H. (New York : McGraw-Hill Irwin, 2011)
The book is geared towards professors who love Garrison's market-leading managerial accounting content, but have been bothered by the debits and credits included in the book. It includes the same coverage of managerial accounting topics such as relevant costs for decision making, capital budgeting decisions, and segment reporting and decentralization without the journal entries. The job-order costing chapter has been extensively rewritten to remove all journal entries. Furthermore, the chapters dealing with process costing, the statement of cash flows, and financial statement analysis have been dropped to enable professors to focus their attention on the bedrocks of managerial accounting - planning, control, and decision making.
&#x000A
Previous ed.: Boston, Mass.: McGraw-Hill/Irwin, 2008.
Includes bibliographical references and index.
oif 23/06/14
Loan
Keywords: Managerial accounting